Third-Party Allogeneic Mesenchymal Stromal Cells Prevent Rejection in a Pre-sensitized High-Risk Model of Corneal Transplantation - Lohan, Paul; Murphy, Nick; Treacy, Oliver; Lynch, Kevin; Morcos, Maurice; Chen, Bingling; Ryan, Aideen E.; Griffin, Matthew D.; Ritter, Thomas (Frontiers in Immunology, 2018)
High-risk cornea transplant recipients represent a patient population with significant un-met medical need for more effective therapies to prevent immunological graft rejection due to heightened anti-donor immune response. In this study, a rat model of pre-existing anti-donor immunity was developed in which corneal allografts were rejected earlier than in non-pre-sensitized recipients. In this model, third-party (non-donor, non-recipient strain) allogeneic mesenchymal stromal cells (allo-MSC) were administered intravenously 7 and 1 days prior to transplantation. Rejection-free graft survival to 30 days post-transplant improved from 0 to 63.6% in MSC-treated compared to vehicle-treated control animals (p = < 0.0001). Pre-sensitized animals that received third-party allo-MSC prior to transplantation had significantly higher proportions of CD45+CD11b+ B220+ monocytes in the lungs 24 h after the second MSC injection and significantly higher proportions of CD4+ FoxP3+ regulatory T cells in the graft-draining lymph nodes at the average day of rejection of control animals. In in vitro experiments, third-party allo-MSC polarized primary lung-derived CD11b/c+ myeloid cells to a more anti-inflammatory phenotype, as determined by cytokine profile and conferred them with the capacity to suppress T cell activation via prostaglandin E2 and TGFβ1. In experiments designed to further validate the clinical potential of the protocol, thawed cryopreserved, third-party allo-MSC were shown to be similarly potent at prolonging rejection-free corneal allograft survival as their freshly-cultured counterparts in the pre-sensitized high-risk model. Furthermore, thawed cryopreserved third-party allo-MSC could be co-administered with mycophenolate mofetil without adversely affecting their immunomodulatory function. In conclusion, a clinically-relevant protocol consisting of two intravenous infusions of third-party allo-MSC during the week prior to transplantation, exerts a potent anti-rejection effect in a pre-sensitized rat model of high-risk corneal allo-transplantation. This immune regulatory effect is likely to be mediated in the immediate post-transplant period through the promotion, by allo-MSC, of alternatively-activated macrophages in the lung and, later, by enhanced regulatory T-cell numbers.